Fundamental Human Rights in the Islamic Perspective - Tuti Gusmawati Simanjuntak; Lili Rahmayana Harahap; Cherry Arida; Yusfani, Muhammad; Bahraini; Cecep Soleh Kurniawan (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Abstracts into the fabric of our humanity. Human rights are a divine gift that enable every individual to fulfill their role as stewards of the Earth (khalifatullah), without any form of discrimination. Despite this, some groups argue that Islamic law does not embrace Western conceptions of human rights, instead seeing it as a framework that focuses primarily on obligations and obedience to divine commands. The method used by researchers aims to describe, understand and explain the object under study based on data obtained through literature data regarding discussions that focus on Human Rights in an Islamic Perspective so that answers can be obtained which can ultimately be explained in detail. Research conducted by this author reveals that the Islamic approach to human rights embodies universal and timeless principles that resonate across cultures. Rather than offering apologies, it is important to acknowledge that Islam has been a pioneer in articulating the concepts of equality, universality, and democracy. As a comprehensive religion, Islam encompasses all dimensions of human existence, guiding individuals towards a holistic understanding of rights and responsibilities.